Biochemical and Physiological Effect of Excess Manganese (Mn) in Bean (Phaseolus vulgaris L. cv. Strike) - Zengin, Fikriye (Natl Acad Sciences India, 2013)
The present work aimed to study the physiological effects of manganese (Mn) in bean (Phaseolus vulgaris L. cv. Strike). Bean seedlings were exposed to increasing doses (0.1, 0.2, 0.3 and 0.4 mM) of manganese chloride (MnCl2 center dot H2O) for 10 days. After 10 days of heavy metal treatment, seedlings were harvested for pigment, proline, protein, ABA (abscisic acid) and vitamin content determinations. Elevated Mn levels increased the ABA content in roots and leaves of seedlings. An increase of proline and vitamin in leaves of seedlings and decrease of chlorophyll (a and b) and total protein contents (p < 0.05 or p < 0.01) occurred on exposure to Mn. Mn level at certain critical points negatively affected seedling growth. These results are important to understand the biological consequences of heavy metal contamination particularly in soil reserved to organic agriculture.
Keywords: Abscisic acid; Chlorophyll (a and b); Manganese; Proline; Total protein; Vitamin